The Impact of Training, Family Environment, and Motivation on Youth Entrepreneurial Interest in WPM Clinic - Jumiyati, Jumiyati; Rachmawati, Ike Kusdyah; Handoko, Yunus (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
In Kutai Kartanegara, the Youth Entrepreneurship Clinic Program (WPM) which has been running since 2019 has succeeded in producing many successful young entrepreneurs. However, participants in this program face many obstacles such as low interest in entrepreneurship due to lack of training, lack of family support, and low motivation. Apart from that, there is also a research gap which shows that training and motivation have no effect on interest in entrepreneurship. This research aims to analyze the influence of entrepreneurship training, family environment, and motivation on youth entrepreneurship interest in the WPM program using a quantitative approach and multiple linear regression analysis and data processing using SPSS 25. From a population of 118 training participants, a sample of 54 people was taken using the Slovin technique and proportional random sampling. The research results show that: 1) Entrepreneurship training does not have a significant effect on youth entrepreneurship interest. 2) The family environment does not have a significant effect on youth entrepreneurship interest. 3) Motivation has a positive and significant effect on youth entrepreneurship interest. 4) Entrepreneurship training, family environment and motivation simultaneously have a significant effect on youth's entrepreneurial interest.